Transient stability of power system with static VAR compensator and power system stabilisers / Norhidayu Abd Hamid - Abd Hamid, Norhidayu (2010)
When increase power transfer, transient stability is increasing important for secure operation. Transient stability evaluation of large scale power system is an extremely intricate and highly non-linear problem. An importance function of transient evaluation is to appraise the capability of the power system to withstand serious contingency in time, some emergencies or preventive control can be carried out to prevent system breakdown. Static VAR compensator (SVC) and Power System Stability (PSS) play an important role as a stability aid for dynamic and transient disturbances in power system. The damping of power system oscillation after a three-phase fault is analyzed with the analyzation of the effects of SVC and PSS on transient stability performance of a power system. The obtained result shows the effected of SVC and PSS on transient stability of power system.